Characterization and compact modeling of self-aligned short-channel organic transistors - Torres-Miranda, Miguel; Sauter, Eric; Zharnikov, Michael (IEEE transactions on electron devices, 2018)
In this paper, we present the characterization and modeling of downscaled flexible organic thin-film transistors fabricated by photolithography and self-alignment of the source and drain contacts to the gate. A SPICE model based on the unified model and extraction method for thin-film transistors (TFTs) is tailored with high accuracy for the subthreshold regime in order to include the channel length dependence of two semiempirical parameters, viz., the effective mobility and the onset voltage. In addition, we demonstrate the modeling of the hump effect, a phenomenon often present in TFTs fabricated by lithographic methods.